ANALISIS PENETAPAN HARGA JUAL RUMAH MENGGUNAKAN METODE HEDONIC PRICE PADA PERUMAHAN TIPE MENENGAH DI KOTA PEKANBARU - Rahmawati, Kiki; Ekwarso, Hendro; ', Taryono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study was conducted in the city of Pekanbaru. Pekanbaru City's economy continues to grow, not triggered by the increasing contributions made by each sector of the economy. The growing economy of Pekanbaru trigger development, be it the construction of public places such as shopping centers, places of worship, hospitals, schools, hotels, and especially housing. The purpose of this study was to determine the selling price determination using hedonic house price on housing medium type in Pekanbaru. Basic sampling in this study using Taro Yamane formula it can be seen the number of samples in this study amounted to 91 homeowners in the medium type of housing in the city of Pekanbaru. Data analysis method used is descriptive analysis method. The results of this study are Determination selling price of homes using hedonic Price On Housing Type Medium in the city of Pekanbaru is done by considering the characteristics of the location of that land area, building area, number of bedrooms and number of bathrooms then consider the environmental characteristics that access to health care, distance to the center education, and crime rates, and considering the quality of the environment is the level of noise and air qualityKeywords: Characteristics Location, Environmental Caracteristics, Environmental Quality, Determination of Hedonic Price Method